2021
DOI: 10.32598/rj.22.2.3011.1
|View full text |Cite
|
Sign up to set email alerts
|

Negative Factors Affecting the Sleep Quality of the Elderly in Iran: A Systematic Review

Abstract: Objective: As age increases, different physical and mental problems, including sleep disorders, occur in the elderly. The Person-Environment-Occupation (PEO) model is one of the most common practical models in occupational therapy. The current study aims to review negative factors affecting the sleeping quality of the elderly in Iran based on the PEO model. Materials & Methods: According to PRISMA (the preferred reporting items for systematic reviews and meta-analyses) guidelines and in this systematic rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Increasing the daily consumption of fruits, meat, and eggs can increase the duration of sleep (41). Physiological factors such as snoring, apnea, and abnormal sleep behavior and duration can also interfere with sleep (42). Studies have found that improving physical activity levels has a positive impact on sleep in older adults (43).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the daily consumption of fruits, meat, and eggs can increase the duration of sleep (41). Physiological factors such as snoring, apnea, and abnormal sleep behavior and duration can also interfere with sleep (42). Studies have found that improving physical activity levels has a positive impact on sleep in older adults (43).…”
Section: Discussionmentioning
confidence: 99%
“…Ramezanifar et al (2021) reported that factors affecting sleep problems were job stress, and shift work, which can impair sleep quality. Therefore, therapists are required to attend to occupational factors in intervention and counseling [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the review article of Mortazavi et al (2021), environmental factors such as economic level, staying in a nursing home, living in an environment with extreme cold or heat, unsuitable physical environments and living in certain areas were reported as effective factors in the sleep disorder of the elderly [21]. Ashghab et al (2022) reported that manipulating environmental factors such as reducing the amount of noise, dimming the ambient light, and using blindfolds and earmuffs can significantly improve sleep quality in nurses [22].…”
Section: Introductionmentioning
confidence: 99%